2022
DOI: 10.3390/life12060848
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Complete Chloroplast Genomes of Eight Ficus Species and Insights into the Phylogenetic Relationships of Ficus

Abstract: The genus Ficus is an evergreen plant, the most numerous species in the family Moraceae, and is often used as a food and pharmacy source. The phylogenetic relationships of the genus Ficus have been debated for many years due to the overlapping phenotypic characters and morphological similarities between the genera. In this study, the eight Ficus species (Ficus altissima, Ficus auriculata, Ficus benjamina, Ficus curtipes, Ficus heteromorpha, Ficus lyrata, Ficus microcarpa, and Ficus virens) complete chloroplast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…To date, vast comparative chloroplast genomic studies have been conducted in a wide range of taxonomic levels, such as order (such as Dipsacales [56] and Saxifragales [57]), family (such as Orchidaceae [58] and Zingiberaceae [59]), and genus (such as Camellia [60], Lindera [61], Gossypium [62], and Ficus [17,51,63]). However, less research has focused on the comparative genomics of taxa undergoing recent speciation, such as the species complex [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, vast comparative chloroplast genomic studies have been conducted in a wide range of taxonomic levels, such as order (such as Dipsacales [56] and Saxifragales [57]), family (such as Orchidaceae [58] and Zingiberaceae [59]), and genus (such as Camellia [60], Lindera [61], Gossypium [62], and Ficus [17,51,63]). However, less research has focused on the comparative genomics of taxa undergoing recent speciation, such as the species complex [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies of comparative chloroplast genomics in Ficus identified entirely different hyper-variable intergenic regions. For example, Xia et al [63] identified trnS-GCU-trnG-UCC, trnT-GGU-psbD, trnV-UAC-trnM-CAU, clpP-…”
Section: Chloroplast Genomic Evolutionary Hotspotsmentioning
confidence: 99%
“…Recently, Huang et al (2022) evaluated the cp genomes of ten species in the Ficus genus. The results showed that Morus and Ficus had a close relationship compared to other genera of the Moraceae family with high bootstrap values [13,55]. In this study, the phylogenetic relationships by ML analyses were constructed based on two approaches, the complete cp genome sequence and the psbA-trnH intergenic spacer region.…”
Section: Discussionmentioning
confidence: 96%